QUALITATIVE CASE STUDY OF CRITICAL SUCCESS FACTOR IN THREE ERP IMPLEMENTATION PROJECTS - Mellyuni Sitinjak; Riyanto Jayadi (Journal of Information System Management (JOISM), 2023)
The COVID-19 pandemic has tremendously impacted every aspect of life worldwide. The ERP implementation project also experienced a considerable impact because each stage of the process was carried out online (limited face-to-face meetings). Project management's unpreparedness in implementing the COVID-19 pandemic is one of the critical success factors discussed in this study. This study presents three qualitative case studies and tries to identify what caused an issue in ERP project implementation during the COVID-19 pandemic by comparing the alignment of PMBOK literature to project methodology practices. This study found that several factors do not meet the lack of efficiency standards based on ERP project implementation standards (SAP Methodology). These factors affect project targets in the main characteristics of each SAP ERP implementation step, namely data integrity and best practices. PMO requires commitment from each stakeholder to carry out project activities according to plan. Project evaluations must be carried out periodically so PMO can still complete the project according to plan. Keywords: Project Management, Project Methodology, PMBOK, ERP, Critical Success Factor